Development of Enzymatic aza-Michael Addition Reactions - Kansal, Isha (My University, 2023)
Enzymes are the biocatalysts which are capable of accelerating biochemical reactions. The utilization of enzymes as catalysts for non-natural reactions has been recognized as a valuable and ecologically sustainable approach in the field of synthetic chemistry. In addition, these catalysts offer significant enantio-, chemo-, and regioselectivity, thereby decreasing the possibility of undesired side reactions. Enzymes have been classified into different categories, including isomerases, ligases, lyases, oxidoreductases, transferases, translocases and hydrolases. Among various types of hydrolases, α-amylase has been employed to facilitate a diverse range of non-natural organic conversions, in addition to its inherent ability to catalyse the hydrolysis of 1,4-glyosidic bonds found in starch. Furthermore, the Michael addition reaction is an important transformation in organic synthesis. Several reports have been published where a diverse range of catalysts have been employed for the aza-Michael addition of aromatic amines to α,β-unsaturated carbonyl compounds. Also, the obtained β- aminocarbonyls serve as active pharmaceutical precursors. Therefore, a green protocol for the aza-Michael addition of benzoyl hydrazine to chalcones using α-amylase from Aspergillus oryzae as biocatalyst in aqueous medium has been devised.
Keywords: Biocatalysis; Enzyme; Michael Addition; Chalcone